Mergers, Stagflation and the Logic of Globalization - Jonathan Nitzan (Rethinking Political Global Economy. Emerging Issues, Unfolding Odysseys, 2003)
The chapter offers a new approach for analysing capitalist development and crisis, tying together mergers and acquisitions, stagflation and globalization as integral facets of accumulation. The framework builds on the concept of differential accumulation, emphasizing the power drive by dominant capital groups to beat the average and exceed the normal rate of return. Four regimes of differential accumulation are articulated: internal breadth by amalgamation, external breadth through green-field investment, internal depth via cost-cutting, and external depth through stagflation. The complex relationships between these different regimes, as well as their broader societal implications, are analysed in light of the US experience over the past century. Several broad conclusions emerge. (1) Of the four regimes, the most important are amalgamation and stagflation, which tend to oscillate inversely to each other. (2) Over the longer haul, amalgamation grows exponentially relative to green-field investment, contributing to the stagnation tendency of modern capitalism. (3) The wave-like pattern of mergers and acquisitions reflects the progressive break-up of socioeconomic `envelopes', as dominant capital moves through successive amalgamation at the industry, sectoral, national, and, finally, global level. In this sense, the current global merger wave is an integral facet of differential accumulation. (4) Periodic lulls in amalgamation tend to be compensated for by stagflation, which appears as a crisis at the societal level, but which contributes significantly to differential accumulation at the disaggregate level. An end to the present worldwide merger boom could therefore trigger global stagflation. (5) Stagflation crises have been previously 'resolved' when dominant capital broke its existing envelope, pushing to amalgamate within a broader universe of takeover targets. Given that there is nothing more to conquer beyond the global envelope, future stagflation crises may prove much more difficult to tame.
Keywords: 330; accumulation; acquisitions; breadth; capital; capitalism; centralization; competition; conflict; conglomeration; corporation; crisis; depth; differential accumulation; distribution; finance; globalization; growth; institutionalism; IPE; liberalization; M&A; merger; ownership; politics; power; profit; ruling class; sabotage; stagflation; state; stock market; technology; TNC; United States; US; violence; war